Pengaruh Pemberian Calcitriol terhadap Kadar Limfosit pada Tikus Putih (Rattus norvegicus) Galur Wistar Jantan yang Dipapar Asap Rokok - Jordy Oktobiannobel; Hetti Rusmini; Retno Ariza Soeprihatini Soemarwoto; Syafa’atun Malihah (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
The health impact for active and passive smokers is damage to the organs and respiratory tract. The body organs initially experience inflammation which increases the number of white blood cells, one of which is an increase in lymphocytes. One of the efforts to reduce the damage caused free radical by cigarette smoke is by consuming Calcitriol. Objective: To determine the effect of presenting Calcitriol on lymphocyte levels in male Wistar rats (Rattus norvegicus) exposed to cigarette smoke. Methods: This type of research is a pure experimental (true-experiment) using a pre and post-test research design with a control group design to check lymphocyte levels in male Wistar rats (Rattus norvegicus). 24 rats were divided into 6 groups simultaneously. Random, namely the control group 1 (exposed to cigarette smoke and not given Calcitriol), group 2 (exposed to cigarette smoke and not given Calcitriol), placebo control group (exposed to cigarette smoke and given olive oil), treatment 1 (exposed to cigarette smoke and given Calcitriol with a dose of 0.25 µgr / head), treatment 2 (exposed to cigarette smoke and given Calcitriol at a dose of 0.5 µgr / head) and treatment 3 (exposed to cigarette smoke and given Calcitriol at a dose of 1 µgr / head). Results: Paired t-test lymphocyte levels showed evidence that stated (p <0.05) in the K2 group (p = 0.014), the K3 group (p = 0.049), the P1 group (p = 0.012) and the P3 group (0.001) . Meanwhile, group K1 (p = 0.115) and group P2 (p = 0.066) had no statistical difference. Conclusion: Calcitriol administration can reduce lymphocyte levels in male Wistar rats exposed to cigarette smoke.